2017
DOI: 10.1038/s41598-017-11422-7
|View full text |Cite
|
Sign up to set email alerts
|

UPLC-Q-TOF/MS-based metabonomic studies on the intervention effects of aspirin eugenol ester in atherosclerosis hamsters

Abstract: Based on the pro-drug principle, aspirin and eugenol were used to synthesize aspirin eugenol ester (AEE) by esterification reaction. In present study, the anti-atherosclerosis effects of AEE were investigated in hamsters with the utilization of metabonomic approach based on UPLC-Q-TOF/MS. Biochemical parameters and histopathological injures in stomach, liver and aorta were evaluated. In atherosclerotic hamster, oral administration of AEE normalized biochemical profile such as reducing TG, TCH and LDL, and sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
3
11
1
Order By: Relevance
“…The HFD‐fed hamster is thought to be a convenient and sensitive model for rapid establishment of atherosclerosis (Singhal, Finver‐Sadowsky, McSherry, & Mosbach, ; Zhao, Chen, Mao, Min, & Cao, ). It had been confirmed that AEE can prevent the severe atherosclerotic lesions in the aorta of HFD‐fed Syrian golden (Ma, Yang, Liu, Kong, et al, ), while the mechanism by which AEE protects against the injury of aorta induced by HFD is still unknown. The metabolomic analysis of HFD‐fed hamsters and AEE‐treated HFD‐fed hamsters suggested that protective effect of AEE against the injury of aorta might be related to a reduction in oxidative stress (Ma, Yang, Liu, Kong, et al, ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The HFD‐fed hamster is thought to be a convenient and sensitive model for rapid establishment of atherosclerosis (Singhal, Finver‐Sadowsky, McSherry, & Mosbach, ; Zhao, Chen, Mao, Min, & Cao, ). It had been confirmed that AEE can prevent the severe atherosclerotic lesions in the aorta of HFD‐fed Syrian golden (Ma, Yang, Liu, Kong, et al, ), while the mechanism by which AEE protects against the injury of aorta induced by HFD is still unknown. The metabolomic analysis of HFD‐fed hamsters and AEE‐treated HFD‐fed hamsters suggested that protective effect of AEE against the injury of aorta might be related to a reduction in oxidative stress (Ma, Yang, Liu, Kong, et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…It had been confirmed that AEE can prevent the severe atherosclerotic lesions in the aorta of HFD‐fed Syrian golden (Ma, Yang, Liu, Kong, et al, ), while the mechanism by which AEE protects against the injury of aorta induced by HFD is still unknown. The metabolomic analysis of HFD‐fed hamsters and AEE‐treated HFD‐fed hamsters suggested that protective effect of AEE against the injury of aorta might be related to a reduction in oxidative stress (Ma, Yang, Liu, Kong, et al, ). In the present study, the oxidative balance was disturbed in plasma of HFD‐fed atherosclerotic hamsters, and AEE treatment significantly attenuated the oxidative imbalance caused by HFD ( P < 0.05).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…At 12 h after the last treatment, the rats were anesthetized with sodium pentobarbital (40 mg/kg, intraperitoneal) ( 73 ) and blood samples were collected into normal vacuum tubes via cardiac puncture. The serum was collected by centrifuging the blood at 2,300 × g at 4°C for 10 min ( 74 ). The liver tissues were also excised under anesthetic conditions, and the serum and liver tissues were stored at -80°C prior to further experimentation.…”
Section: Methodsmentioning
confidence: 99%